Pengaruh Penggunaan Media Film Sebagai Sumber Belajar IPS Terpadu Terhadap Hasil Belajar IPS Terpadu Kelas VII MTS Al-Falah Muncak - Kurniawan, Putut Wisnu (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
This study aims to determine whether there is influence of the use Media Movies on learning outcomes IPS students. The data collection was done by using the test as the principal method, as well as complementary techniques using interviews, observation, and literature. In analyzing the data, the writer used t-test formula it is obtained t hit = 3,87, while for significant level of 5% for t daf = 2,00 and while for significant t daf = 2,66. It can be concluded that thit = 3.87> 2.00 and 3.87> 2.66. It can be concluded there is influence by using the medium of film to the learning outcomes in class VII MTs. Al-Falah Muncak 2016-2017 school year with an average value in the experimental class is X1 = 76.2, while those not using Media Film X2 reached a value of 61.8.